Penyalagunaan Wewenang Kepala Desa Dalam Membuat Surat Keterangan Tanah - Tuhuleruw, Ilona Miranda; Bakarbessy, Andress Deny; Matitaputty, Merlien Irene (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The village head is part of the government apparatus at the lowest level, playing an important role in helping to achieve legal certainty regarding land rights.Purposes of the Research:  The purpose of the current research is to know and analyze what authority the village head has in making a land certificate and to know and analyze what the legal consequences are if there is an abuse of the village head's authority in making a land certificateMethods of the Research: The research method in this study is normative legal research, using a statutory and conceptual approach. Sources of research data include primary, secondary, tertiary legal sources. The data collection technique is in the form of literature study. Processing and analysis of legal materials used in writing is using a qualitative analysis method.Results of the Research: The result of the research show that it was found that abuse of authority was found in the case of land acquisition for the AL wharf in Tawiri Ambon City, unscrupulous village heads abused authority in making land certificates for land sale and purchase transactions in 2015, the letter was made by for his personal interests and verified by the sub-district head ambon bay.